Human Resource Management Strategies in Fashion Show Event at Polbeng Business Expo Chapter II - Indriyani Leoren (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The purpose of this study is to describe the Human Resource Management (HRM) strategies applied in the implementation of Fashion Show activities at Polbeng Business Expo Chapter II. This study focuses on the application of HRM strategies, including the selection process, training, empowerment, and performance appraisal of the organizing committee in supporting the success of the event. A descriptive qualitative approach with a case study method was employed, and data were collected through observation, interviews, and documentation involving committee members and other parties directly engaged in the fashion show activities. The findings indicate that the HRM strategies implemented played an important role in improving coordination, establishing a clear division of responsibilities, and enhancing committee performance during the preparation and implementation of the event. However, several challenges were identified, including limited preparation time, communication barriers among committee members, and differences in work experience. Despite these obstacles, the committee successfully completed its responsibilities through effective coordination and collaboration. The implementation of HRM strategies also contributed to the development of teamwork, responsibility, leadership, and problem-solving skills among committee members. The selection process ensured that individuals were assigned according to their abilities, while training improved their understanding of assigned tasks and event procedures. Empowerment encouraged active participation in decision-making, and performance appraisal provided feedback to evaluate achievements and identify areas for improvement. Overall, this study highlights the importance of applying effective HRM strategies in student-organized events to improve organizational effectiveness and support the successful achievement of event objectives.